Zero-Based Budgeting versus Management Strategy and Applicability: An Applied Study In Municipalities Of Anbar Governorate - Hamzah N. Al-Jumaili; Malik Ahmed Awad (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the feasibility of applying zero-based budgeting in themunicipalities of Anbar Governorate in Iraq, verifies the existence of a writtenstrategy for its adoption, analyzes available resources and capabilities, andproposes a practical model for its implementation.This study uses a descriptive and analytical approach through data collection andanalysis. A survey research tool "questionnaire" was used, designed to achieve thestudy objectives, and distributed to 280 municipal employees, including managers,accountants, and local council members, to assess their perceptions of applyingzero-based budgeting. In addition, interviews were conducted with senior officialsto obtain their vision towards implementing zero-based budgeting in theirdepartments and whether it is in their minds and strategies. The results of our studyindicate major gaps in current practices, including the absence of a clear strategyfor adopting zero-based budgeting, insufficient financial resources, lack of skilledemployees, insufficient technological infrastructure, weak administrative support,and the absence of legislative frameworks supporting the implementation of thistype of budgeting. The study also identified critical areas for improvement,including developing a clear strategy, enhancing staff capacity through training,enhancing administrative support, upgrading technological resources, andreviewing legal frameworks to support the foundations of zero-based budgeting.The findings underscore the need for a comprehensive and well-supportedtransition plan to successfully implement zero-based budgeting in Anbarmunicipalities. By addressing these challenges, municipalities can improve resource allocation, prioritize projects more effectively, and ultimately enhancefinancial management practices. The paper concludes with a proposed model thatrepresents the basic steps that should be adopted initially when embarking on thezero-based budgeting process, to ensure the successful implementation of zero-based budgeting.